2019
DOI: 10.24106/kefdergi.3393
|View full text |Cite
|
Sign up to set email alerts
|

Kültürel Miras ve Korunmasına İlişkin Ortaokul Öğrencilerinin Görüşleri

Abstract: İnsanlığın ürünü olarak kültür toplumsal ve tarihi nitelik taşımaktadır. Kültürel miras ise toplumların en önemli zenginlik unsurlarından birini oluşturur. Bu araştırmanın amacı ortaokul öğrencilerinin kültürel miras ve kültürel mirasın korunması konusundaki görüşlerini belirlemektir. Araştırma nitel verilere dayanan ve betimsel nitelik taşıyan bir çalışmadır. Araştırmaya beşinci ve altıncı sınıfa devam eden 186 ortaokul öğrencisi katılmıştır. Araştırma verilerinin çözümlenmesinde içerik analizi kullanılmıştır… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
1
2
0
4
Order By: Relevance
“…The results are similar to the definitions in literature related to common heritage (Kiper, 2004;Uçar, 2014;Şakacı, 2015;Göğebakan, 2009;Avcı and Memişoğlu, 2016). It can be said that this result is also similar to the results of Gürdoğan Bayır and Çengelci Köse's (2019) research. The majority of the students answered the question of why it is important to preserve the common heritage as historical importance, universal value, and transfer to future generations, contribution to tourism, development of social relations, cultural importance and aesthetic characteristics.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 90%
See 1 more Smart Citation
“…The results are similar to the definitions in literature related to common heritage (Kiper, 2004;Uçar, 2014;Şakacı, 2015;Göğebakan, 2009;Avcı and Memişoğlu, 2016). It can be said that this result is also similar to the results of Gürdoğan Bayır and Çengelci Köse's (2019) research. The majority of the students answered the question of why it is important to preserve the common heritage as historical importance, universal value, and transfer to future generations, contribution to tourism, development of social relations, cultural importance and aesthetic characteristics.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 90%
“…In the seventh grade, it is aimed to introduce the concept of common heritage to the students with the acquisition of "Be aware of the responsibility of humanity in keeping the products of thought, art and literature, natural assets and historical environments alive as common heritage elements." Although it was observed that there is academic studies regarding cultural heritage (Yeşilbursa, 2011;Uçar, 2014;Avcı and Memişoğlu, 2016;Gürdoğan Bayır and Çengelci Köse, 2019), there were very few studies on common heritage, especially in terms of educational sciences (Göğebakan, 2009). This study apart from the concept of cultural heritage studies focuses on concept of common heritage.…”
Section: Introductıonmentioning
confidence: 99%
“…Bu araştırmalar, ağırlıklı olarak öğrenciler, öğretmenler ve aday öğretmenlerle yürütülmüştür. İlk gruptaki araştırmalarda, daha çok öğrencilerin kültürel mirasla ilgili alanlar hakkındaki bilgi (Akkaya, 2017), deneyim (Aslan ve Çulha, 2008), görüş (Gürdoğan-Bayır ve Çengelci-Köse, 2019;Gürel ve Çetin, 2019;Karakuş, Çepni ve Kılcan, 2011) algı (Levy, 2016;Tuncel ve Altuntaş, 2020), tutum (Arıkan ve Doğan, 2013;Dönmez ve Yeşilbursa, 2014;Ismaeel ve Al-Abdullatif, 2016) ve farkındalık (Sağ ve Ünal, 2019;Uztemur, Dinc ve Acun, 2019) durumlarının değerlendirildiğini söylemek mümkündür. İkinci grupta, öğretmenlerle yapılan çalışmalarda (Adukaite, van Zyl, Er ve Cantoni, 2017;Avcı ve Memişoğlu, 2016;Giménez, Ruiz ve Listán, 2008;Kafol, Dena ve Znidarsic, 2015;Lee ve Bang, 2011;Levy, 2016;Özlek, 2019;Pérez, López ve Listán, 2010), çeşitli branşlardaki öğretmenlerin kültürel miras konuları ve öğretimi hakkındaki görüşlerine başvurulmuştur.…”
Section: İlgili Araştırmalarunclassified
“…These studies have been predominantly carried out with students, teachers, and teacher candidates. It can be seen that the students' knowledge, viewpoint, perception, attitude, and awareness of the areas relevant to cultural heritage were assessed in the studies of the first group (Akkaya, 2017;Arıkan and Doğan, 2013;Aslan ve Çulha, 2008;Dönmez and Yeşilbursa, 2014;Gürdoğan-Bayır and Çengelci-Köse, 2019;Gürel and Çetin, 2019;Ismaeel and Al-Abdullatif, 2016;Karakuş, Çepni and Kılcan, 2011;Levy, 2016;Sağ and Ünal, 2019;Tuncel and Altuntaş, 2020;Uztemur, Dinc and Acun, 2019). In second group studies have focused on the insights of teachers in different branches on cultural heritage issues and its teaching (Adukaite, van Zyl, Er and Cantoni, 2017;Avcı and Memişoğlu, 2016;Giménez, Ruiz and Listán, 2008;Kafol, Dena and Znidarsic, 2015;Lee and Bang, 2011;Levy, 2016;Özlek, 2019;Pérez, López and Listán, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Alanyazında konu ile ilgili öğrencilerin tutum, algı, bilinç ve farkındalık düzeylerini belirlemek amacıyla yapılan çalışmalara (Gümüş & Adanalı, 2011;Yeşilbursa, 2011;Kılcan & Akbaba, 2013;Selanik Ay & Kurtdere Fidan, 2013;Yeşilbursa, 2013;Dönmez & Yeşilbursa, 2014;Akkuş vd., 2015;Demirbulat vd., 2015;Çelepi, 2016;Karaca Yılmaz vd., 2017;Yıldırım Saçılık & Toptaş, 2017;Güneş & Alagöz, 2018;Cihangir & Köksal, 2019;Halaç vd., 2019;Mancı, 2019;Gök, 2020;Kendir, 2020;Günden, 2021;Halaç vd., 2021) rastlanmaktadır. Bununla birlikte, turizm rehberliği bölümü öğrencilerinin SOKÜM değerleri hakkındaki bilgi ve deneyim düzeyleri ile SOKÜM değerlerine yönelik tutumlarının belirlenmesine yönelik çalışmaların (Bişkin & Adabalı, 2018;Köroğlu vd., 2018;Gürdoğan Bayır & Çengelci Köse, 2019;Sağ & Ünal, 2019;Sarı vd., 2020;Günden & Güneren, 2021)…”
unclassified